Interoceptive autonomic regulation in typical development and autism spectrum disorder: A computational model integrating multiple physiological systems - Ruichen Li; Hao Liu; Yukie Nagai (PLoS ONE, 2026)
Background Interoceptive cardiovascular signals, including heart rate (HR) and blood pressure (BP), arise from coordinated sympathetic (SNS) and parasympathetic (PSNS) regulation and contribute to affective and cognitive processes. Although atypical autonomic nervous system (ANS) modulation has been reported in autism spectrum disorder (ASD), the dynamical structure underlying branch-specific coordination remains insufficiently characterized. Objective To estimate latent ANS regulatory structure in typically developing (TD) and ASD individuals using a computational modeling framework. Methods A closed-loop computational model integrating cardiovascular, respiratory, and autonomic dynamics was developed. ANS regulation was formalized using three autonomic control modes (coupled reciprocal, coupled nonreciprocal, and uncoupled) and parameterized by effective modulation weights of SNS and PSNS. HR and BP responses to the head-up tilt (HUT) test were simulated, and regulatory surfaces were compared with empirical HR and BP data from TD and ASD groups. Additional simulations under normal respiration, deep respiration, and absence of respiration evaluated mean arterial pressure (MAP) regulation across varying SNS–PSNS activity combinations. Results TD individuals exhibited differentiated SNS–PSNS coordination patterns across control modes, whereas ASD individuals showed convergence of SNS–PSNS weight. In TD, HR and BP distributions under coupled reciprocal mode were most consistent with expected physiological responses, characterized by high SNS and low PSNS activity during postural challenge. In ASD, empirical data extended toward regions associated with relatively higher PSNS weighting, suggestive of persistent parasympathetic engagement during postural challenge. Incorporation of deep respiration enhanced MAP reduction during BP recovery, particularly under over-elevated SNS activity. Conclusion This study provides a mechanistic, state-space characterization of autonomic coordination in TD and ASD populations, enabling inference of latent autonomic regulation from measurable interoceptive phenotypes and identifying respiration as a model-based regulatory lever that augments cardiovascular stabilization.